Dairy Enterprise – 100 Lactating Cows (Freestall) - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 2006)
This publication examines the cost and returns for a dairy operation with 100 lactating cows in a freestall system.
MF272_2006_10
Keywords: MF272; Livestock; Economics; MF